MX1: a bending‐magnet crystallography beamline serving both chemical and macromolecular crystallography communities at the Australian Synchrotron. (1st January 2015) - Cowieson, Nathan Philip; Aragao, David; Clift, Mark; Ericsson, Daniel J.; Gee, Christine; Harrop, Stephen J.; Mudie, Nathan; Panjikar, Santosh; Price, Jason R.; Riboldi‐Tunnicliffe, Alan; Williamson, Rachel; Caradoc‐Davies, Tom
<x xml:space="preserve">Abstract</x> MX1 is a bending‐magnet crystallography beamline at the 3 GeV Australian Synchrotron. The beamline delivers hard X‐rays in the energy range from 8 to 18 keV to a focal spot at the sample position of 120 µm FWHM. The beamline endstation and ancillary equipment facilitate local and remote access for both chemical and biological macromolecular crystallography. Here, the design of the beamline and endstation are discussed. The beamline has enjoyed a full user program for the last seven years and scientific highlights from the user program are also presented.